Top Management Team Horizontal Pay Disparity and Firm’s R&D Investments - Ahn, Ji-Young(안지영); Kim, Bong-Jin(김봉진) (대한경영학회지, 2011)
This study explores the effects of top management team (TMT) horizontal pay disparity on firm's R&D investments. Drawing on two literatures – status characteristics theory and power – we argue that top executives’ pay level will act as an indicator of their value to the firm and that high levels of pay disparity within the TMT will result in perceived or actual power differences within the team. This high pay disparity within the TMT could possibly result in hindering various team processes and consequently negatively affect firm's innovation investments. We construct different measures of TMT horizontal pay disparity and use publicly archived firm data to test our hypotheses. The results provide evidence that greater horizontal pay disparity within the TMT does result in lesser investments in firm’s innovative capacity, suggesting that power differences hinder team collaboration processes. This study explores the effects of top management team (TMT) horizontal pay disparity on firm's R&D investments. Drawing on two literatures – status characteristics theory and power – we argue that top executives’ pay level will act as an indicator of their value to the firm and that high levels of pay disparity within the TMT will result in perceived or actual power differences within the team. This high pay disparity within the TMT could possibly result in hindering various team processes and consequently negatively affect firm's innovation investments. We construct different measures of TMT horizontal pay disparity and use publicly archived firm data to test our hypotheses. The results provide evidence that greater horizontal pay disparity within the TMT does result in lesser investments in firm’s innovative capacity, suggesting that power differences hinder team collaboration processes. KCI Citation Count: 0